Meningkatkan Hasil Belajar Pak Dalam Materi Pribadi yang Unik Menggunakan Model PBL (Problem Based Learning) dengan Media Video Youtube pada Kelas IV Fase B SD Joannes Bosco Kota Yogyakarta - Yulius Swantoro; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The learning method that has been applied in Grade IV at Joannes Bosco Elementary School Yogyakarta is less engaging. It affects the students’ performance. They show less cooperation. On the other hand, the expected achievement targets are not to be met. This research aims to improve the Gotong Royong dimension character and achievement targets through the implementation of a problem-based learning (PBL) model assisted by YouTube video media. This classroom action research was conducted in two cycles with the theme